(untitled) (Zoo Botanica, 2025)
The optimum nutrient management offers a pathway to resource-efficient and sustainable crop production. Usually, the farmers frequently misunderstand the association between crop growth and N application. Thus, the exploration of most favorable nitrogen level is the dire need of Maize growers. Therefore, a field experiment consisting of seven nitrogen application rates viz; T1= No nitrogen (control), T2= Nitrogen@ 75 kg ha-1, T3= Nitrogen @ 100 kg ha-1, T4= Nitrogen @ 125 kg ha-1 (recommended), T5= Nitrogen @ 150 kg ha-1, T6= Nitrogen @ 175 kg ha-1 and T7= Nitrogen @ 200 kg ha-1 were tested under randomized complete block design (RCBD).The highest plant height (cm), leaves plant-1, nodes plant-1, stem girth (cm), fodder weight (g plant-1) and fodder yield (t ha-1) were noted @ 200 kg ha-1. However, nitrogen at 200 kg ha-1did not vary notably by 175 kg ha-1 for all studied traits. The lowest performance of yield and yield components were noted in control plots. Thus, it is advised to achieve the maximum fodder production of Maize variety Akbar, the crop must be supplied with nitrogen @ 175 kg ha-1under agro-climatic conditions of Tandojam.